Comparing Attained Weight and Weight Velocity during the First 6 Months in Predicting Child Undernutrition and Mortality. Issue 1 (21st September 2021) - Wang, Dongqing; Schwinger, Catherine; Urassa, Willy; Berhane, Yemane; Strand, Tor A; Fawzi, Wafaie W
ABSTRACT: Background: The first 6 mo of life are critical for subsequent risk of undernutrition and mortality. The predictive abilities of attained weight at the end of each month and monthly weight velocity for undernutrition and mortality need to be compared. Objectives: This study aimed to examine the predictive abilities of different weight metrics during the first 6 mo of life in predicting undernutrition and mortality. Methods: This study used a cohort of infants in Tanzania. Weight and length were measured monthly from birth to 18 mo of age. Three weight metrics during the first 6 mo of life were considered as predictors, including attained weight-for-age z score (WAZ) at the end of each month, monthly change in WAZ, and monthly weight velocity z score (WVZ). Logistic models were used with undernutrition (at 6 or 12 mo) and mortality (over the first 18 mo) as outcomes. AUC values were compared across metrics. Results: For predicting wasting at 6 mo, WVZ (AUC: 0.80) had a greater predictive ability than attained WAZ (AUC: 0.76) and change in WAZ (AUC: 0.71) during the second month of life. After 2 mo, attained WAZ (AUC: 0.81–0.89) had greater predictive abilities than WVZ (AUC: 0.71–0.77) and change in WAZ (AUC: 0.65–0.67). For predicting stunting at 6 mo, attained WAZ (AUC: 0.75–0.79) had consistently greater predictive abilities than WVZ (AUC: 0.56–0.66) and change in WAZ (AUC: 0.50–0.57). The weight metrics had similar abilities in predicting mortality, with the AUC rarely reaching >0.65. Conclusions: Attained weight at the end of each month had greater abilities than monthly weight velocity in the same month in predicting undernutrition. Attained weight remains a useful indicator for identifying infants at greater risk of undernutrition.